AYURVEDA MANAGEMENT OF DYSFUNCTIONAL UTERINE BLEEDING - A CASE REPORT (International Journal of Ayurveda and Pharma Research, 2015)
A 41yrs. female patient came to our clinic outpatient department Gune Ayurved College, Ahmednagar, Maharashtra with complaints of excessive vaginal bleeding. The case was diagnosed as Adhoga Raktapitta by Ayurvedic nidan, symptomatic relief by Stambhana dravyas was not ultimate solution to avoid hysterectomy. This case was successfully treated on basic principles of Ayurveda Panchbhautic chikitsa. A symptom free follow up in this case was noticed after completion of 8 months Ayurved therapy. The treatment options offered here primary aim at reducing Kshardharmiushnata in the body with Parthivdravya and increasing uterine tone (Dharana).Dysfunctional Uterine Bleeding is defined as a state of abnormal uterine bleeding without any clinically detectable organic, systemic & iatrogenic cause. Heavy Bleeding interferes with womens physical emotional, social & material quality & life. Currently DUB is defined as a state of abnormal uterine bleeding following anovulation due to dysfunction & hypothalamo-pituitary-ovarian axis endocrine origin. It is more prevalent in premenopausal & abortion. Overall 70%-80% results of endometrial ablation or resection amongst 10% of the patients need hysterectomy. In present case study we are presenting here with more than 2 yrs. history of Dysfunctional Uterine Bleeding without any response from modern medicine.